Active Role of Women in Disaster Prone Areas - Ratnanik Ratnanik; Yulinda Erma Suryani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Indonesia is a country that has two (2) seasons, namely the rainy season and the dry season. Klaten Regency is close to Mount Merapi, east of the Klaten area close to the Dengkeng River and its tributaries. Disaster management law No. 4 of 2007 article 4 paragraph c states that ensuring the implementation of disaster management in a planned, integrated, coordinated and comprehensive manner and respecting local culture. This study discusses the higher vulnerability of women compared to men, so that it requires handling that requires more active roles of women residents or volunteers. The aim of this research is to see how active women's roles are in disaster disasters and what roles women play in the context of disasters. From the results of the study it can be concluded that the active role of women in disaster-prone areas in Klaten Regency has begun to be trained. Evidenced by joining the Disaster Risk Reduction Organization (OPRB) in Klaten